The Effect of Promotion, Brand Image and Social Media on Customer Purchase Decision at Fritto Chicken Sumarsono - Alimin, Erina; Tanny , Felix Emmanuel (Jurnal Ilmiah Global Education, 2024)
The promotion activity carried out during the year 2023 at Fritto Chicken Sumarsono Branch in Medan were found to be quite a lot, but the promotions conducted on social media platforms through Fritto chicken accounts show a limited reach to customers, resulting in a lack of awareness and participation in purchase decision. Does Promotion have partially effect on customer purchase decision at Fritto Chicken Sumarsono branch, Does brand image have partially effect on customer purchase decision at Fritto Chicken Sumarsono branch, Does social media have partially effect on customer purchase decision at Fritto Chicken Sumarsono branch, Do Promotion, brand image and social media have simultaneous effect on customer purchase decision at Fritto Chicken Sumarsono branch. This research uses quantitative research. The sample in this study was 97 respondents with the criteria: Costumers who are above 18 years old, Gender Male and Female, Customers who have made purchases at least once at Fritto Chicken Sumarsono. The basic data for this study was collected through interviews with the supervisor and surveys administered to customers of the Fritto Chicken Sumarsono branch in Medan. The research and analysis conducted with validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, coefficient of determination test, the multiple linear regression. The research results show that Promotion has partial effect on the consumer purchase decision. Brand image has partial effect on the consumer purchase decision. Social media has partial effect on the consumer purchase decision. Promotion, brand image, and social media effect customer purchase decision simultaneously at Fritto Chicken Sumarsono branch.